2000
DOI: 10.1152/ajpheart.2000.279.4.h1906
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator mechanisms in the coronary circulation of endothelial nitric oxide synthase-deficient mice

Abstract: Previous studies have demonstrated that responses to endothelium-dependent vasodilators are absent in the aortas from mice deficient in expression of endothelial nitric oxide synthase (eNOS -/- mice), whereas responses in the cerebral microcirculation are preserved. We tested the hypothesis that in the absence of eNOS, other vasodilator pathways compensate to preserve endothelium-dependent relaxation in the coronary circulation. Diameters of isolated, pressurized coronary arteries from eNOS -/-, eNOS heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 40 publications
3
69
0
Order By: Relevance
“…44 However, in the eNOS -/-, overall total endothelium-dependent dilation of the coronary vasculature can be either unaltered, 83 reduced, 44 or eliminated 82 when compared to WT littermates. Since dilatory responses to endothelium-independent dilators in eNOS -/-are identical to those in WT in both isolated vessels 82,83 and perfused heart preparations, 40,44 these results suggest that alterations occur in the eNOS -/-as a result of changes in the activity of other endothelium-derived vasodilators to compensate for the loss of eNOS-derived NO.…”
Section: Coronary Hemodynamics and Vasomotor Activity In The Enos Knomentioning
confidence: 99%
See 2 more Smart Citations
“…44 However, in the eNOS -/-, overall total endothelium-dependent dilation of the coronary vasculature can be either unaltered, 83 reduced, 44 or eliminated 82 when compared to WT littermates. Since dilatory responses to endothelium-independent dilators in eNOS -/-are identical to those in WT in both isolated vessels 82,83 and perfused heart preparations, 40,44 these results suggest that alterations occur in the eNOS -/-as a result of changes in the activity of other endothelium-derived vasodilators to compensate for the loss of eNOS-derived NO.…”
Section: Coronary Hemodynamics and Vasomotor Activity In The Enos Knomentioning
confidence: 99%
“…The coronary vasculature of WT mice depends on NO for the majority of its overall total endothelium-dependent dilation since acute NOS inhibition eliminates most of the ACh-induced dilation in isolated preparations of the left anterior descending and left circumflex coronary arteries 82,83 and about half of the bradykinin (BK)-induced dilation in isolated heart preparations. 44 However, in the eNOS -/-, overall total endothelium-dependent dilation of the coronary vasculature can be either unaltered, 83 reduced, 44 or eliminated 82 when compared to WT littermates.…”
Section: Coronary Hemodynamics and Vasomotor Activity In The Enos Knomentioning
confidence: 99%
See 1 more Smart Citation
“…32 In each case the compensatory PG dilator was derived from the endothelium. 31,32 These data suggest that certain vessels have the ability to compensate for the loss of one endothelium-dependent vasodilator mechanism by upregulating an alternative endothelium-dependent dilator system (EDHF or prostaglandins).…”
Section: Hatoum Et Al Novel Nonendothelial Release Of Pgd 2 2359mentioning
confidence: 99%
“…9,30 Lamping et al showed that in coronary arteries from wild-type mice, dilation to Ach is mediated primarily by NO, whereas in endothelial NO synthase knockout mice, the dilation is dependent on activity of neuronal nitric oxide synthase and COX. 31 Sun et al showed that flow-induced dilation is mediated by both endothelial NO and prostaglandins in skeletal muscle arterioles from wild-type mice, but is mediated exclusively by prostaglandins in male endothelial NO synthase knockout mice. 32 In each case the compensatory PG dilator was derived from the endothelium.…”
Section: Hatoum Et Al Novel Nonendothelial Release Of Pgd 2 2359mentioning
confidence: 99%